LANGUAGE TO ITS ROLE - MAS DARUL IHSAN (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2017)
Every people in the world use their own way to express their idea, feeling and thought. It is impossible for people to express their perception, emotions, categorization, abstraction processes, and reasoning without having a concept of language. Language plays the great role in human being life. Because, language itself is not only about as a system of verbal signs which serve to formulate thoughts in the process of reflecting objective reality by subjective cognition, and to communicate socially those thoughts about reality, as also the related emotional, aesthetic, volitional, and experiences. But also Language is a purely human and non-instinctive method of communicating ideas, emotions and desires by means of a system of voluntarily produced. Then, in having the discussion of a connection of a language into its role, it will be refers to language in terms of acquisition and communicative competence, it is about cultural variation in children’s conversation; language to identity; the relevance of the ethnography of communication to language teacher; language in terms of participation; language in terms of conversation analysis; and language ideology